Environmental Ethics and Information Asymmetry among Organizational Stakeholders - Kulkarni, Subodh P. (Journal of business ethics, 2000)
This paper addresses the conflicting environmental interests of a firm and the community, an important stakeholder. The short-term profit maximization objective of a firm may stand in contrast with what the community wants – a "safe and clean environment". This paper argues that the information regarding the environmental impact of a firm's products, processes, and waste may be asymmetrically distributed between the firm and the community. The resultant information asymmetry may influence the probability of a firm acting opportunistically, and ultimately, a firm's ethical behavior. The paper identifies information asymmetry between a firm and community, as well as that within the community. The perceived information asymmetry across various community segments may perhaps be a determinant of environmental discrimination. The paper further contends that information asymmetry may diminish in the long run. Finally it examines the implications of information asymmetry for firms and government policy.